O ensino da física da atmosfera utilizando um objeto de aprendizagem: olhares e percepções dos professores do ensino médio - Silva, Nyla Nynab Ferreira (Universidade Federal Rural do Semi-Árido, 2017)
The focus of this work is to approach Atmospheric Physics in High School using a learning object, a software specially developed to teach about the terrestrial atmosphere using physical concepts and also that allows to work other Physics contents such as: Thermology, Hydrostatics, Modern Physics and Quantum. Interdisciplinarity is an active factor in software, besides Physics, Chemistry, Geography and Biology are sciences present in the course of the study on the Atmosphere. The creation of the software was developed, aiming to work with the current technologies to which the students of the High School are inserted and for verifying that the majority of the books of Physics do not approach on the Physics of the Atmosphere and if it does, it establishes in the form of sections, Box or hypertexts. Few are the works that propose some methodology of teaching and learning with respect to the teaching of Atmospheric Physics in the current school. The validation of the software was carried out with forty-eight teachers, students of the National Professional Master's in Physics Teaching (MNPEF), the Quixadá and Mossoró poles. In the application, the Instruction Manual for the use of the software was read, the presentation of the Learning Object and finally the application of a questionnaire of twenty six questions that sought to know the training of the teacher, as occurs the teaching of Physics of Atmosphere in High School and teachers' opinions regarding the use of software in the classroom. The result of the questionnaire carried out with the master teachers showed that Atmospheric Physics Software possesses excellent qualities in the educational and technological aspects, being a significant tool for the teaching of Physics, thus leaving the student interested in learning about the Physics of the Atmosphere and consequently learning other contents of Physics covered in this
Keywords: Ensino de física; Física da atmosfera; Objeto de aprendizagem; Software; Teaching physics; Physics of the atmosphere; Learning object; Software; CIENCIAS EXATAS E DA TERRA::FISICA